Home-based transcranial direct current stimulation in mild neurocognitive disorder due to possible Alzheimer’s disease. A randomised, single-blind, controlled-placebo study - Satorres, Encarnacion; Escudero Torrella, Joaquin; Real, Elena; Pitarque, Alfonso; Delhom, Iraida; Melendez, Juan C. (Frontiers in Psychology, 2023)
Introduction Mild neurocognitive disorder (mNCD), a pre-dementia stage close to Mild Cognitive Impairment, shows a progressive and constant decline in the memory domain. Of the non-pharmacological therapeutic interventions that may help to decelerate the neurodegenerative progress, transcranial direct current stimulation (tDCS) shows beneficial effects on the learning curve, immediate recall, immediate verbal memory and executive functions. The purpose of this research was to study the effect of tDCS on general cognition, immediate and delayed memory and executive functions by comparing an active group with a placebo group of mNCD patients. Methods Participants were 33 mNCD due to possible AD, randomly assigned to two groups: 17 active tDCS and 16 placebo tDCS. Ten sessions of tDCS were conducted over the left dorsolateral prefrontal cortex. Several neuropsychological scales were administered to assess the primary outcome measures of general cognitive function, immediate and delayed memory and learning ability, whereas the secondary outcome measures included executive function tests. All participants were evaluated at baseline and at the end of the intervention. Mixed ANOVAs were performed. Results Significant effects were obtained on general cognitive function, immediate and delayed memory and learning ability, with increases in scores in the active tDCS group. However, there were no significant effects on executive function performance. Conclusion The present study demonstrated the effectiveness of tDCS in an active tDCS group, compared to a placebo group, in improving general cognition and immediate and delayed memory, as previous studies found. Taken together, our data suggest that tDCS is a simple, painless, reproducible and easy technique that is useful for treating cognitive alterations found in neurodegenerative diseases.